2016
DOI: 10.1038/cddis.2016.252
|View full text |Cite
|
Sign up to set email alerts
|

RBM24 suppresses cancer progression by upregulating miR-25 to target MALAT1 in nasopharyngeal carcinoma

Abstract: Abnormal interaction between non-coding RNAs has been demonstrated to be a common molecular event in various human cancers, but its significance and underlying mechanisms have not been well documented. RNA-binding proteins (RBPs) are key regulators of RNA transcription and post-transcriptional processing. In this study, we found that RNA-binding protein 24 (RBM24) was frequently downregulated in nasopharyngeal carcinoma (NPC). The restoration of RBM24 expression suppressed NPC cellular proliferation, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 53 publications
3
57
1
Order By: Relevance
“…The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also known as nuclear-enriched transcript 2 (NEAT2), is a lncRNA consisting of more than 8700 nt located on chromosome 11q13 and acts as a transcriptional regulator for various genes including those involved in cell proliferation, migration and metastasis. Several studies have shown that the aberrant expression of MALAT1 is found in various cancer types, and associated with clinical progression in human cancers including NPC [89-91]. LncRNA MALAT1 was highly expressed in 5-8F cells with a high metastatic potential compared to that in normal nasopharyngeal epithelium cells.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also known as nuclear-enriched transcript 2 (NEAT2), is a lncRNA consisting of more than 8700 nt located on chromosome 11q13 and acts as a transcriptional regulator for various genes including those involved in cell proliferation, migration and metastasis. Several studies have shown that the aberrant expression of MALAT1 is found in various cancer types, and associated with clinical progression in human cancers including NPC [89-91]. LncRNA MALAT1 was highly expressed in 5-8F cells with a high metastatic potential compared to that in normal nasopharyngeal epithelium cells.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…Many lncRNAs, such as MALAT1, H19, and HOTAIR have been demonstrated as critical regulator of carcinogenesis and development of many cancers [8-12]. LncROR was first discovered in induced pluripotent stem cells (iPSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, has‐miR‐615‐3p and MCM4 were identified to serve as new biomarkers for NPC via gene expression profiles GSE12452 (31 NPC and 10 normal samples) and GSE53819 (18 NPC and 18 normal samples), as well as miRNA expression profiles GSE32960 (312 NPC and 18 normal samples) and GSE36682 (62 NPC and six normal samples) obtained from the GEO database . Additionally, RBM24 is demonstrated to be a tumor suppressor in NPC after retrieval of the mRNA expression profiles from two data sets GSE12452 and GSE53819 . By contrast, in our study, the differentially expressed genes c9orf24, PCDP1, and LRRC46 related to NPC were retrieved in the data set GSE53819 were only comprised of 18 NPC and 18 normal samples.…”
Section: Discussionmentioning
confidence: 61%
“…44 Additionally, RBM24 is demonstrated to be a tumor suppressor in NPC after retrieval of the mRNA expression profiles from two data sets GSE12452 and GSE53819. 45 By contrast, in our study, the differentially expressed genes c9orf24, PCDP1, and LRRC46 related to NPC were retrieved in the data set GSE53819 were only comprised of 18 NPC and 18 normal samples. Therefore, c9orf24, PCDP1, and LRRC46 are not the only key genes related to NPC, and further studies are needed to compare the efficacy of these genes above.…”
Section: Degs Mebluementioning
confidence: 82%